Index - from issues 1 to 100 (November 1996): No. 01 - 100 - Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1996)
An index of articles from issues 25 to 100 of the Plant Genetic Resources Newsletter and from issues 1 to 24 of the FAO Plant Introduction Newsletter, the previous title of the publication.